Is there a potential of misuse for Magnolia officinalis compounds/metabolites?. (18th May 2017) - Schifano, Fabrizio; Guarino, Valentina; Papanti, Duccio G.; Baccarin, Jacopo; Orsolini, Laura; Corkery, John M.
Abstract: Objective: Magnolia bark contains magnolol, metabolized to tetrahydromagnolol and honokiol, with both GABA‐ergic/cannabimimetic activities, hence of possible attraction to vulnerable individuals/recreational misusers. Methods: A literature review, assessment of related anecdotal online Magnolia misuse's reports and an overview of Magnolia products' online acquisition possibilities has been here described. Results: No peer‐reviewed papers about Magnolia abuse/misuse/dependence/addiction were identified. Conversely, from a range of websites emerged potentially 3 groups of Magnolia misusers: (a) subjects with a psychiatric history already treated with benzodiazepines, being attracted to Magnolia bark as a "natural sedative"; (b) polydrug misusers, ingesting Magnolia with a range of other herbs/plants, attracted by the GABA‐ergic/cannabimimetic activities; (c) subjects naive to the misusing drugs' scenario, perceiving Magnolia as a natural dietary supplement/weight‐control compound. Conclusions: To the best of our knowledge, this is the first paper commenting on the possible Magnolia derivatives' potential of misuse. Magnolia's recent increase in popularity, mainly as a sedative, may be arguably due to its peculiar pharmacological properties/acceptable affordability levels/virtually worldwide favorable legal status and customers' attraction to a product being perceived as "natural" and hence somehow "safe." Future/potent/synthetic magnolol and honokiol structural analogues could however contribute to increasing the number of synthetic GABA‐ergic/cannabimimetic misusing compounds.